Comparison of Child Health between Sandwich Generation and Non-Sandwich Generation - Sri Yuliana (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2021)
Sandwich Generation must treat two generations simultaneously and undoubtedly, having an impact on health in the sandwich generation, the previous generation, and the following generations. This study used IFLS data in 2007 and 2014 because IFLS provides longitudinal data that can see the relationship between sandwich generation households and children’s health status with the Multinomial Logistics Regression method. The results showed that the BMI of non-sandwich generation children was higher than the group of sandwich generation children and was statistically significant, so it was concluded that there were differences in the average BMI between groups of sandwich generation children and non-sandwich generation children. BMR of sandwich generation children is lower than the group of not sandwich generation children and statistically significant, so with these results, it can be concluded that there is a difference in the average BMR between groups of sandwich generation children and non-sandwich generation children. The status of sandwich generation where relative to non-sandwich generation is only significant if the child is obese. Meanwhile, the status of the sandwich generation, which is relative to non-sandwich generation, significantly affects BMR for children in both the below-average BMR category and above-average BMR category for the overall sample.